Mood-congruent free recall bias in anxiety. - Russo, R; Fox, E; Lynn, B; Nguyen-Van-Tam, D (2001)
The present study evaluated the status of mood-congruent free recall bias in anxious individuals following incidental encoding of target words. In the first experiment, high trait anxiety individuals showed increased recall of threat-related information after an orienting task promoting lexical processing of target words. In a second experiment, both lexical and semantic orienting tasks were performed at study. In this experiment, anxious individuals displayed a mood-congruent recall bias only for target information processed at a lexical level. Theoretical and practical implications of these findings are discussed.